AN EXTENDED TPB MODEL OF GREEN HOUSING PURCHASE INTENTION: EVIDENCE FROM INDONESIA’S URBAN HOUSING MARKET - Ulya Zaen Cahyani; Yoga Triwikananda; Istijanto; Karyadi Gunawan; Rizkya Fadhma; Ruth Artha Sovia Napitupulu (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2026)
Green housing purchase intention is an important issue in sustainable urban development in Indonesia. This study examines the determinants of green housing purchase intention by extending the Theory of Planned Behaviour (TPB). The model incorporates environmental concern, perceived value, reasonable price, and green product attributes to represent behavioural and economic factors influencing consumer decisions. A quantitative survey was conducted among 286 urban respondents, and the data were analysed using multiple regression. The results indicate that purchase attitude is the strongest predictor of purchase intention. Perceived value and environmental concern have significant positive effects, while perceived behavioural control shows a weaker influence. Subjective norms and reasonable price are not significant. In addition, green product attributes significantly influence purchase attitude, highlighting tangible environmental features shaping consumer perceptions. These findings emphasize the importance of strengthening consumer attitudes and perceived value to encourage green housing adoption.